The German Version of the Gaze Anxiety Rating Scale (GARS): Reliability and Validity. - Gregor Domes; Lisa Marx; Ines Spenthof; Markus Heinrichs (PLoS ONE, 2016)
Objective Fear of eye gaze and avoidance of eye contact are core features of social anxiety disorders (SAD). To measure self-reported fear and avoidance of eye gaze, the Gaze Anxiety Rating Scale (GARS) has been developed and validated in recent years in its English version. The main objectives of the present study were to psychometrically evaluate the German translation of the GARS concerning its reliability, factorial structure, and validity. Methods Three samples of participants were enrolled in the study. (1) A non-patient sample (n = 353) completed the GARS and a set of trait questionnaires to assess internal consistency, test-retest reliability, factorial structure, and concurrent and divergent validity. (2) A sample of patients with SAD (n = 33) was compared to a healthy control group (n = 30) regarding their scores on the GARS and the trait measures. Results The German GARS fear and avoidance scales exhibited excellent internal consistency and high stability over 2 and 4 months, as did the original version. The English version's factorial structure was replicated, yielding two categories of situations: (1) everyday situations and (2) situations involving high evaluative threat. GARS fear and avoidance displayed convergent validity with trait measures of social anxiety and were markedly higher in patients with GSAD than in healthy controls. Fear and avoidance of eye contact in situations involving high levels of evaluative threat related more closely to social anxiety than to gaze anxiety in everyday situations. Conclusions The German version of the GARS has demonstrated reliability and validity similar to the original version, and is thus well suited to capture fear and avoidance of eye contact in different social situations as a valid self-report measure of social anxiety and related disorders in the social domain for use in both clinical practice and research.